2007
DOI: 10.1017/s003118200700323x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat fragmentation on wild mammal infection by Trypanosoma cruzi

Abstract: Expansion of human activities frequently results in habitat fragmentation, a phenomenon that has been widely recognized in the last decades as one of the major threats to world's biodiversity. The transformation of a continuous forest into a fragmented area results in a hyper-dynamic landscape with unpredictable consequences to overall ecosystem health. The effect of the fragmentation process on Trypanosoma cruzi infection among small wild mammals was studied in an Atlantic Rain Forest landscape. Comparing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
59
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 23 publications
9
59
0
2
Order By: Relevance
“…Philander frenatus and M. nudicaudatus are mainly terrestrial marsupials, commonly observed in fragmented landscapes (Pinto et al 2009, Vieira et al 2009). Even species with arboreal habits, and thus relatively more susceptible to deforestation, such as M. incanus, M. (M.) paraguayana and G. microtarsus, have frequently been observed in small forest fragments (Olifiers 2002, Castro & Fernandez 2004, Pardini et al 2005, Vaz et al 2007). The low capture success of these marsupials as well as rodent species in this study may be a consequence of the high habitat disturbance, caused mainly by forest fragmentation in the study areas (Lumbreras et al 2004, Fundação SOS Mata Atlântica & INPE 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Philander frenatus and M. nudicaudatus are mainly terrestrial marsupials, commonly observed in fragmented landscapes (Pinto et al 2009, Vieira et al 2009). Even species with arboreal habits, and thus relatively more susceptible to deforestation, such as M. incanus, M. (M.) paraguayana and G. microtarsus, have frequently been observed in small forest fragments (Olifiers 2002, Castro & Fernandez 2004, Pardini et al 2005, Vaz et al 2007). The low capture success of these marsupials as well as rodent species in this study may be a consequence of the high habitat disturbance, caused mainly by forest fragmentation in the study areas (Lumbreras et al 2004, Fundação SOS Mata Atlântica & INPE 2015.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,24,42 This separation is not complete because other DTUs have occasionally been found in opossums and armadillos. 4,7,23,43 The most likely local vectors of TcI and TcIII, as yet not identified conclusively, are Triatoma sordida and Panstrongylus geniculatus, respectively. Triatoma sordida is locally abundant and was the only bug species found infected with TcI 31 whereas P. geniculatus was found in local armadillo burrows.…”
Section: Discussionmentioning
confidence: 99%
“…Residual forest fragments act as a refuge for some host species. The effects of habitat fragmentation on disease prevalence vary with the specific host-parasite relationship, 23,54 and new foci of transmission may be created at intermediate levels of degradation. 23 Some of the main reservoir hosts of T. cruzi adapt easily to peridomestic rural environments where they maintain sizable numbers and high prevalence of infection with T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations